2021
DOI: 10.1101/2021.09.28.461924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nasopharyngeal Microbiota as an early severity biomarker in COVID-19 hospitalised patients: a retrospective cohort study in a Mediterranean area

Abstract: Background: There is mounting evidence suggesting that the microbiome composition could be different in COVID-19 patients. However, the relationship between microbiota and COVID-19 severity progression is still being assessed. This study aimed to analyse the diversity and taxonomic composition of the nasopharyngeal microbiota, to determine its association with COVID-19 clinical outcome. Methods and Findings: Samples came from a retrospective cohort of adult patients with COVID-19, hospitalised in a tertiary ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Also, the same diversity was reported in the analysis of speci c kinds of microbiota; in microbial alpha-diversity [48, 57, 65, 76] and beta-diversity [65,76]. In contrast, changes in microbial indices were reported byMaria Paz Ventero et al as lower microbial alpha-diversity and higher betadiversity among deceased COVID-19 patients [74]. Another study showed a signi cant reduction of taxonomic features richness in beta-diversity in COVID-19 patients [48].…”
Section: Upper Respiratory Tract Microbiotasupporting
confidence: 54%
See 2 more Smart Citations
“…Also, the same diversity was reported in the analysis of speci c kinds of microbiota; in microbial alpha-diversity [48, 57, 65, 76] and beta-diversity [65,76]. In contrast, changes in microbial indices were reported byMaria Paz Ventero et al as lower microbial alpha-diversity and higher betadiversity among deceased COVID-19 patients [74]. Another study showed a signi cant reduction of taxonomic features richness in beta-diversity in COVID-19 patients [48].…”
Section: Upper Respiratory Tract Microbiotasupporting
confidence: 54%
“…In the current review, 24 studies discussed the role of URT microbiota in the pathogenesis of COVID-19 infection. The impact of URT microbiota on the preservation of the lung immune system is one of the important aspects as it correlates with respiratory infections [45,74,162]. Unusual changes in URT microbiota in COVID-19 patients, especially moderate and severe patients, were reported in comparison to healthy individuals [21,45].…”
Section: Upper Respiratory Tract Microbiotamentioning
confidence: 99%
See 1 more Smart Citation